The development of inovirus-associated vector vaccines using phage-display technologies - Stern, Zachariah; Stylianou, Dora C; Kostrikis, Leondios G (Expert review of vaccines, 2019)
: Inovirus-associated vectors (IAVs) are derived from bacterial filamentous viruses (phages). As vaccine carriers, they have elicited both cellular and humoral responses against a variety of pathogens causing infectious diseases and other non-infectious diseases. By displaying specific antigen epitopes or proteins on their coat proteins, IAVs have merited much study, as their unique abilities are exploited for widespread vaccine development. : The architectural traits of filamentous viruses and their derivatives, IAVs, facilitate the display of specific antigenic peptides which induce antibody production to prevent or curtail infection. Inoviruses provide a foundation for cost-efficient large-scale specific phage display. In this paper, the development of different applications of inovirus-based phage display vaccines across a broad range of pathogens and hosts is reviewed. The references cited in this review were selected from established databases based on the authors' knowledge of the study subject. : The importance of phage-display technology has been recently highlighted by the Nobel Prize in Chemistry 2018 awarded to George P. Smith and Sir Gregory P. Winter. Furthermore, the symbiotic nature of filamentous viruses infecting intestinal F strains offers an attractive platform for the development of novel vaccines that stimulate mucosal immunity.